(untitled) (European Journal of Marketing and Economics, 2022)
Today, measuring sustainability level of a tourist destination is one of the main obstacles to achieve sustainable tourism (Zamfir - Corbos, 2015). Indeed, sustainability assessment remains a difficult task because of subjectivity unavoidable in this process (McKercher, Mak, - Wong, 2014). Moreover, destination stakeholders’ find the scientific methods very sophisticated and often incomprehensible. In this context, it is necessary to develop new instruments theoretically solid and feasible to measure the sustainable development of a tourist destination. Indeed, identification and measurement are the main unresolved problems of sustainable development because of the difficulties arising from the ill-defined nature of sustainability concept and the diversity of tourism stakeholders in a tourist destination (Farsari - Butler, 2007). The conflict of interest of stakeholders and the simplicity induced by this approach can cut the role of indicators to marketing argument without impacting the sustainability of the destination (Rajaonson and Tanguay, 2010). As a result, the Delphi method is an alternative approach that fills the inadequacies of the two previous approaches. It involves submitting indicators from the consensual policy process to scientist’s evaluation to assess their relevance and applicability. The present paper proposes an alternative method of measuring sustainability of a destination; it presents the results of a Delphi survey conducted at local level of destination to measure the tourism transition towards sustainability. The results of these expert surveys highlight the list of indicators used for sustainable development monitoring; it is both recognized by the experts and acceptable destination’s stakeholders.